Mass Dictatorship and Memory as Ever Present Past - Lim, Jie-Hyun. author. aut Link
XII, 253 p.
Keywords: This volume explores the politics of memory involved in 'coming to terms with the past' of mass dictatorship on a global scale. Considering how a growing sense of global connectivity and global human rights politics changed the memory landscape, the essays explore entangled pasts of dictatorships.